MAX-MIN EDGE MAGIC AND ANTIMAGIC LABELING - J. Jayapriya; K. Thirusangu (European Scientific Journal, ESJ, 2013)
In this paper we introduce a new type of edge magic and antimagic labeling and study the same for various classes of graphs.